2004
DOI: 10.1111/j.1462-2920.2004.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction denaturing gradient gel electrophoresis analysis of the N2‐fixing bacterial diversity in soil under Acacia tortilis ssp. raddiana and Balanites aegyptiaca in the dryland part of Senegal

Abstract: Denaturing gradient gel electrophoresis (DGGE) of amplified nifH gene fragments was used to study the diazotrophic community of soil samples under Acacia tortilis ssp. raddiana (legume tree) and Balanites aegyptiaca (non-legume tree), two dominant plant species growing naturally in the dryland part of Senegal. Samples were taken along transects from the stem up to 10 m distance from it, at depths of 0-0.25 m and 0.25-0.50 m. Sampling was done in the dry season (25 June 1999) and in the rainy season (28 August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Several of the above-cited studies were found to have been limited by the resolution of the culture-independent methods used (clone libraries of limited coverage, ribosomal DNA fingerprinting using eubacterial primers) (23). Supporting this conclusion, a significant correlation between particular plants and soil bacterial populations could be detected when the diazotrophic community was analyzed separately and at high resolution by amplifying the specific functional gene nifH (13); Rhizobium spp. were found to be less diverse in pastures planted with soybeans (11).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Several of the above-cited studies were found to have been limited by the resolution of the culture-independent methods used (clone libraries of limited coverage, ribosomal DNA fingerprinting using eubacterial primers) (23). Supporting this conclusion, a significant correlation between particular plants and soil bacterial populations could be detected when the diazotrophic community was analyzed separately and at high resolution by amplifying the specific functional gene nifH (13); Rhizobium spp. were found to be less diverse in pastures planted with soybeans (11).…”
mentioning
confidence: 54%
“…Specific associations between particular plant species and soil bacterial populations have so far been documented for a few individual groups, like diazotrophic (13,24) or dissimilatory (24) nitrate-reducing bacteria. In the current study, however, 20 out of the 160 sequence types analyzed were found at increased abundance in lysimeters devoid of higher plant species.…”
Section: Discussionmentioning
confidence: 99%
“…As direct amplification failed, to increase sensitivity, the nifH gene fragments were retrieved by nested PCR. Demba Diallo et al (7) explained that direct amplification failed using PolF and AQER in the first PCR due to quite a low nifH copy number compared with the other nifH gene pools in the sample. Another possible explanation is contamination, by inhibiting substances (e.g., humic acids), of the DNA extracted from soil samples (38).…”
Section: Pcr Amplification Targeting the Nifh Genementioning
confidence: 99%
“…Although there have been many attempts to describe the diversity of nifH gene pools in environmental samples (6,7,9,12,19,30,31,33), few studies have simultaneously displayed both qualitative and quantitative differences in nifH gene composition (18,26,27,32). Phylogenetic trees have been frequently used to describe visually the microbial diversity in diverse environments.…”
Section: Diversity Of the Nifh Gene In The Rhizosphere Of M Malabathmentioning
confidence: 99%
See 1 more Smart Citation